Sadtong Panahon: Oral Storytelling Training Course for Pre-Service Teachers - Marigrace D. Carretero; Jackielyne M. Bosquillos; Jhonner D. Ricafort (Philippine Association of Institutions for Research, Inc., 2016)
Storytelling is an art that contributes not only to students' academic success, but also to their emotional well-being. However, not many teachers have skills in storytelling. The reason maybe that they have not been trained in the art, or they lack knowledge of it. The study identified the different reactions of the students during storytelling sessions as observed by the students themselves and the teachers. The study is both quantitative and qualitative in nature. It made use of a descriptive developmental research design. The respondents were 60 students and 60 teachers. Survey questionnaires were used to gather data. Unstructured interviews were also conducted to validate their answers. Results showed that most of the students are bored and do not engage themselves during the storytelling session. This may be attributed to poor skills in forming connections and poor communication skills of the teachers. Based on the findings, it can be concluded that teachers' way of telling a story affects the students' understanding and interest in the story. However, this skill is lacking in most teachers. Varied problems related to these skills are met by the teachers. The researchers recommend that teachers need to improve their communication skills to become effective storytellers and a storytelling training course should be designed and implemented to train pre-service teachers and enhance their storytelling skills.